The role of host phenology in determining the incidence of an insect sexually transmitted infection. Issue 5 (10th September 2015) - Pastok, Daria; Hoare, Mary‐Jo; Ryder, Jon J.; Boots, Mike; Knell, Rob J.; Atkinson, David; Hurst, Gregory D. D.
Abstract : Changes in the timing of life history events within the year alter the degree to which the activity patterns of different species coincide, making the dynamics of interspecific interactions sensitive to the phenology of the interacting parties. For parasites, the availability of suitable hosts to infect represents a crucial determinant of dynamics, and changes in the host (and parasite) phenology may thus alter disease epidemiology and the conditions for disease maintenance. We tested the hypothesis that the incidence of a sexually transmitted mite infection, Coccipolipus hippodamiae, in Adalia bipunctata ladybird beetles in Sweden was determined by host phenology, namely presence/absence of sexual contact between cohorts of the host. We observed that the pattern of mite presence/absence across Swedish A. bipunctata populations was highly reproducible between years, implying a persistent biological/ecological basis underlying the incidence. Further, ladybirds from populations where the mite was absent were able to acquire mites during copulation, develop a mite infection, and transmit infection onward, indicating an ecological (rather than biological) driver of mite incidence. Observations of ladybird phenology in natural populations provided evidence of sexual contact between overwintered and new cohort adults in populations where the mite was present. In contrast, new cohort ladybirds in the two northern Swedish populations where the mite was not present had not had sexual contact with the overwintered generation, creating a 'hard stop' to mite transmission. We conclude that variation in host phenology may be an important driver of the incidence of sexually transmitted infections (STIs) by determining the presence/absence of sexual contact between generations. More generally, we hypothesize that sensitivity to variation in host phenology will be highest for parasites like STIs that infect one host species, one host life stage and are directly transmitted on contact between host individuals.